Effects of increasing amounts of true ileal digestible lysine on the growth performance of growing-finishing pigs reared in a commercial facility - R O Gottlob; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2006)
Two 28-d experiments using 2,259 gilts were conducted to determine the growth and economic effects of increasing dietary true ileal digestible (TID) lysine in commercially reared growing-finishing pigs. Both experiments included 6 dietary treatments of incrementally increasing TID lysine in diets containing 6% added fat. The dietary TID lysine ranged from below to above our current requirement estimates to determine if there were any changes in lysine requirements during the past five years. In Exp. 1, pigs were initially 132 lb and averaged 192 lb at the end of the 28-day study. The TID lysine rates were 0.65, 0.75, 0.85, 0.95, 1.05, and 1.15%, which corresponded to lysine:calorie ratios of 1.80, 2.08, 2.35, 2.63, 2.91, and 3.19 g/Mcal, respectively. Increasing TID lysine increased ADG (linear, P<0.01) and improved F/G (quadratic, P<0.06), with optimal performance at 1.05% TID lysine (TID lysine:ME ratio of 2.91 g/Mcal). Pigs fed this diet consumed approximately 22 g of TID lysine per day, and used 21.6 g of TID lysine/kg of gain. Although not significant, margin over feed cost (MOF) was numerically greatest for pigs fed 1.05% TID. In Exp. 2, pigs were initially 177 lb and averaged 241 lb at the end of the 28-d study. The TID lysine rates were 0.52, 0.62, 0.72, 0.82, 0.92, and 1.02%, which corresponded to lysine:calorie ratios of 1.44, 1.71, 1.99, 2.27, 2.55, and 2.83 g/Mcal, respectively. In Exp. 2, the optimal TID lysine rate changed over the course of the experiment. During the first 14 d, pigs fed 0.92% TID lysine had the greatest ADG and lowest F/G, whereas pigs fed 0.72% TID lysine had the numerically highest ADG and lowest F/G from d 14 to 28. Pigs fed these diets required approximately 19.5 g of TID lysine/kg gain. Margin over feed costs increased (quadratic, P<0.03) with increasing dietary TID lysine, with the greatest return at 0.72% TID lysine. In summary, results of the first experiment suggest an increase in dietary TID lysine recommendations, compared with our earlier studies. Even though the optimal lysine rate may be changing over time for this genetic line and production facility, it seems that using the estimate of approximately 20 g TID lysine per kg of gain will provide a good estimate of the pig's lysine requirement.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Finishing pig; Energy; Lysine; Growth; Swine